Pentingnya pertimbangan tanggung jawab sosial perusahaan dalam penetapan tujuan pelaporan keuangan dalam conceptual framework pelaporan keuangan Indonesia - Suwaldiman Suwaldiman (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2000)
Conventional financial statements focus on the result of business transactions. Exhanges between a firm and its social environment are practicially ignored. Exchanges between a firm and society consist primarily of the result is a social cost, and if they lead to an increase in social resources, the result is a social benefit.The responsibility of the social cost and social benefit of a business entity is held on the management. however, there is no a framework that can be based on a guideline to measure and report the social costs and social benefits. Therefore, there are not accuinting standards (particularly in Indonesia) for the social costs and social benefits. It is difficult to measure the management responsibility in an accounting report for the social costs and social benefits without the standards. Because of an accounting standard is derived from a conceptual framework, it s needed to develop the conceptual framework for financial reporting that is socially concerned.